Automatic green fruit counting in orange trees using digital images - Maldonado, Walter [UNESP]; Barbosa, José Carlos [UNESP] (Elsevier, 2016)
Yield estimation is an important factor in a production process planning. In the case of citrus crops, can be useful in industrial management and as guidance for farmers, showing a decisive role in the product market strategies and cultivation practices. Several techniques are being studied for estimating citrus crop yield. On the basis of the known correlation between the number of visible fruits in a digital image and the total of fruits present in an orange tree, we developed a method for green fruit feature extraction with a combination of the techniques of color model conversion, thresholding, histogram equalization, spatial filtering with Laplace and Sobel operators and Gaussian blur. In addition, we built and tested an algorithm to recognize and count them, with detection rates of false-positives of 3% in images acquired in good conditions. It is possible to estimate the mean number of visible fruits in the trees within a tolerated error of 5% with up to 46 images and taking approximately 8 min without any human interaction.
Keywords: Citrus; Computer vision; Fruit detection; Precision agriculture; Yield estimation